Perlindungan Hukum Terhadap Usaha Mikro Kecil Menengah (UMKM) Sebagai Mitra Usaha Ketika Terjadi Kepailitan Perusahaan - Arimba Rivaldo; Joko Sriwidodo; Maryano Maryano (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The purpose of this study is to evaluate and explain how business partners are protected and compensated during a company's bankruptcy. This study employs both a normative juridical and a legislative methodology. The study's findings indicate that attempts to safeguard and settle the law can be made in two ways: (1) by submitting to the bankruptcy institution in order to produce justice; and (2) by referring to Bankruptcy Law No. 37 of 2004. The bankruptcy research findings are a manifestation of the debtor's failure to run the business. Thus, the best course of action is to prioritize legal protection for MSMEs as business partners. The government must pay attention to the business partners of bankrupt companies, as business partners are only a subset of small and medium businesses that exist to fill the needs of these companies, so that when the company goes bankrupt, the small and medium businesses that are also a subset of the company's activities do not have to go bankrupt as well.